MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS DAN KARAKTER WASAKA PADA MUATAN IPAS MENGGUNAKAN MODEL PBL, NHT, DAN SNOWBALL THROWING TERINTEGRASI STEAM PADA SISWA KELAS V SEKOLAH DASAR - Pratiwi, Annisa; Annisa, Muhsinah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The problem in this study is the low critical thinking skills and WASAKA character in the IPAS content of fifth-grade elementary school students. The solution to this problem is to use a combination of the Problem Based Learning, Numbered Heads Together, and Snowball Throwing models integrated with STEAM. The purpose of this study is to analyze students' critical thinking skills and WASAKA character. This study uses Classroom Action Research (CAR) conducted in two cycles. The research subjects are fifth-grade elementary school students, totaling 21 students. The results of this study indicate that students' critical thinking skills were achieved at a rate of 95% with the criterion of very critical and WASAKA character traits were achieved at a rate of 100% with the criterion of already ingrained.